2018
DOI: 10.1007/s12021-018-9372-2
|View full text |Cite
|
Sign up to set email alerts
|

Validation and Optimization of BIANCA for the Segmentation of Extensive White Matter Hyperintensities

Abstract: White matter hyperintensities (WMH) are a hallmark of small vessel diseases (SVD). Yet, no automated segmentation method is readily and widely used, especially in patients with extensive WMH where lesions are close to the cerebral cortex. BIANCA (Brain Intensity AbNormality Classification Algorithm) is a new fully automated, supervised method for WMH segmentation. In this study, we optimized and compared BIANCA against a reference method with manual editing in a cohort of patients with extensive WMH. This was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 22 publications
1
32
0
Order By: Relevance
“…To represent our entire dataset adequately, we selected our training dataset in terms of the WMH loads based on the median values of the Fazekas scores. Ling and colleagues (2018) showed better results with a mixed WMH load training dataset than with a training dataset with only high WMH load as Griffanti and colleagues (2016) suggested in their paper.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…To represent our entire dataset adequately, we selected our training dataset in terms of the WMH loads based on the median values of the Fazekas scores. Ling and colleagues (2018) showed better results with a mixed WMH load training dataset than with a training dataset with only high WMH load as Griffanti and colleagues (2016) suggested in their paper.…”
Section: Discussionmentioning
confidence: 72%
“…With the global threshold in BIANCA this was not the case. Ling and colleagues (2018) validated BIANCA with different input modalities (FLAIR or FLAIR + T1w), with a cohort of patients with CADASIL using a semi-manually generated gold standard of 10 images per sequence. In their dataset, which contained an extremely high WMH load, they received a median DSC of 0.79 (our median 2D FLAIR = 0.560) for the 2D FLAIR + T1w images and a median DSC of 0.78 (our median DSC 3D FLAIR = 0.615) for the 3D FLAIR + T1w images.…”
Section: Discussionmentioning
confidence: 99%
“…Nine of them also used additional datasets or patient data from clinics. Out of 37, twelve studies reported using data from prospective studies or clinics (Atlason et al, 2019;Bowles et al, 2017;Guerrero et al, 2017;Hong et al, 2020;Moeskops et al, 2018;Ling et al, 2018;Park et al, 2018;Qin et al, 2018;Rincón et al, 2017;Roy et al, 2015;Sundaresan et al, 2019;Wang et al, 2015). Four studies used data from the Alzheimer's Disease Neuroimaging Initiative (ADNI) (Sudre et al, 2017;Dadar et al, 2017a;Rachmadi et al, 2018Rachmadi et al, , 2020, of which only two declared the subset used (Rachmadi et al, 2018(Rachmadi et al, , 2020.…”
Section: Sample Characteristicsmentioning
confidence: 99%
“…Twelve studies used data only acquired at 1.5T, and twelve used data only acquired at 3T. Only 11/37 studies used data acquired at both 1.5T and 3T (Atlason et al, 2019;Dadar et al, 2017a;Jiang et al, 2018;Knight et al, 2018;Li et al, 2018;Ling et al, 2018;Liu et al, 2020;Manjón et al, 2018;Sundaresan et al, 2019;Wang et al, 2015;Wu, Zhang, Wang & Tang, 2019).…”
Section: Risk Of Bias Assessment Within Studiesmentioning
confidence: 99%
See 1 more Smart Citation